Exploring the Relationship between Academic Achievement and Emotional Intelligence in Upper Primary School Students - Krisnawati; Irwan; Yusnan, Muhammad; Acoci (The Indonesian Institute of Science and Technology Research, 2024)
This study investigates the relationship between academic achievement and emotional intelligence among upper primary school students. The research, conducted in SD Negeri 1 Rukuwa, Sulawesi Tenggara, explores the levels of emotional intelligence and learning success among 48 participants. The findings reveal that most students exhibit moderate emotional intelligence while learning success is distributed across low, moderate, and high categories. Statistical analyses, including correlation coefficients and regression models, indicate a limited impact of emotional intelligence on academic achievement. The results suggest that other factors such as attention, interest, talent, maturity, preparation, intelligence, and logical intelligence may significantly influence learning success. The study contributes valuable insights into the complex interplay between emotional intelligence and upper primary education academic achievement.